IMPROVING THE EDUCATIONAL PROCESS BASED ON A PEDAGOGICAL INNOVATIVE APPROACH - Farokhat Mirzaeva , Nargiza Mirsagatova , Ogiljan Abdullaeva , Iroda Rejemetova, Feruzaxon Raximova (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The article presents pedagogical innovations of the technological approach to the professional training of bachelors, providing a purposeful change, improving the characteristics of the elements of the methodological system of a higher educational institution. Resources of different learning technologies are considered as innovations.